Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1029/2004gl021295
|View full text |Cite
|
Sign up to set email alerts
|

A proper monsoon index for seasonal and interannual variations of the East Asian monsoon

Abstract: [1] This study assesses how well the East Asian monsoon index (EAMI), developed on the basis of zonal and meridional land -sea thermal contrasts over the AsiaPacific region, can represent the seasonal and interannual variations of the East Asian summer and winter monsoons (EASM and EAWM). It suggests that the EAMI can be used to estimate the timing of the onset and the relative intensity of the EASM, characterized by dominant meridional circulation and rainfall patterns over the Asia-Pacific region, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 18 publications
3
53
0
Order By: Relevance
“…There is remarkable interannual and interdecadal variability of EAWM [5][6][7][8][9]. The out-of-phase relationship between ENSO and EAWM variation was documented by Webster and Yang [10], Zhang et al [11], and Lau and Nath [12].…”
mentioning
confidence: 99%
“…There is remarkable interannual and interdecadal variability of EAWM [5][6][7][8][9]. The out-of-phase relationship between ENSO and EAWM variation was documented by Webster and Yang [10], Zhang et al [11], and Lau and Nath [12].…”
mentioning
confidence: 99%
“…In the years of strong summer monsoon, the rainbelt rushes quickly over northern China and causes drought in the Yangtze River Valley and wetness along the northern boundary of the EASM (Tao and Chen, 1987). As the intensity of the EASM is significant in determining the northern extension of the summer monsoon, it is reasonable to conclude that the intensity of the monsoon is related to the beginning of the flood season in this (Guo, 1983;Tao et al,1987;Zhao and Zhang, 1996;Shi andZhu, 1996 Lu andChan, 1999;Sun et al, 2001;Wang, 2001;Zhang and Liu, 2003;Zhang et al, 2003a, b;Guo et al, 2004;Huang, 2004;Lian et al, 2004;Lee et al, 2005;Zhao and Zhou, 2005;Zhu et al, 2005). Guo et al (2004) reconstructed the index of summer monsoon (Ism) on the basis of the sea level pressure record (SLP) from 1873 to 2000.…”
Section: Easm Change and The Beginning Of Flood Seasonmentioning
confidence: 98%
“…In particular, a stronger EASM is accompanied by decreased rainy days and precipitation amount over the region of the Huaihe River and the middle and lower reaches of the Yellow River (Zhang and Liu, 2003;Zhang et al, 2003a,b;Zhu et al, 2005), while such conditions tend to result in more rainy days and precipitation amounts over northern China (Guo et al, 2004). The intensity of the EASM is an important factor influencing the rainfall pattern over eastern China.…”
Section: Easm Change and The Beginning Of Flood Seasonmentioning
confidence: 99%
“…On both seasonal and interannual time scales, both atmospheric and oceanic forcing contribute to heat content and temperature variations in the YS. The prominent feature of atmospheric circulation influencing this region is the East Asian Monsoon (EAM) system including the East Asian Winter Monsoon (EAWM) and the East Asian Summer Monsoon (EASM) [Tao and Chen, 1987;Zeng, 2002, 2003;Zhu et al, 2005;Wang et al, 2009a]. Analyses of atmospheric reanalysis products showed that wind fields associated with the EAWM and EASM have notable interannual variations with periods of 3-4 and 2-3 years, respectively [Cai et al, 2011].…”
Section: Introductionmentioning
confidence: 99%